2022
DOI: 10.1200/jco.21.02546
|View full text |Cite
|
Sign up to set email alerts
|

Regarding the Children's Oncology Group AEWS1031 Trial for Ewing Sarcoma

Abstract: The article by Leavey et al 1 reported results of the AEWS1031 trial, which investigated the effects of the addition of vincristine, topotecan, and cyclophosphamide (VTC) to interval compressed chemotherapy (ICC) versus ICC in patients with nonmetastatic Ewing Sarcoma (ES). The trial failed to meet its primary end points. No differences in event-free survival (EFS) and overall survival (OS) were observed between the experimental and the control groups (5-year EFS 78% v 79%; P 5 .192; 5-year OS 86% v 88%, P 5 .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…We agree with Wang et al 1 that outcomes as they relate to local control are an important aspect of therapy for patients with nonmetastatic Ewing sarcoma. The group of patients in which the effect of local control modalities can be assessed is a subpopulation of all patients who enroll, and the appropriate outcome measures are EFS and overall survival from the time of local control.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…We agree with Wang et al 1 that outcomes as they relate to local control are an important aspect of therapy for patients with nonmetastatic Ewing sarcoma. The group of patients in which the effect of local control modalities can be assessed is a subpopulation of all patients who enroll, and the appropriate outcome measures are EFS and overall survival from the time of local control.…”
supporting
confidence: 90%
“…We appreciate the comments by Wang et al 1 and the opportunity to add further clarity to our recent article. 2…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Nonetheless, some studies have shown that increasing chemotherapy intensity did not improve Ewing sarcoma efficacy. 8 , 9 , 27 Chemotherapy occupied only one part in the multidisciplinary comprehensive treatment of Ewing sarcoma, and local control modalities had an important impact on long‐term survival. This study also explored the prognosis of different local control modalities and found that surgery combined with radiotherapy was significantly better than surgery alone or radiotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some studies have shown that increasing chemotherapy intensity did not improve Ewing sarcoma efficacy 8,9,27 . Chemotherapy occupied only one part in the multidisciplinary comprehensive treatment of Ewing sarcoma, and local control modalities had an important impact on long‐term survival.…”
Section: Discussionmentioning
confidence: 99%